Revisión especial a la gestión administrativa y su incidencia en la calidad de servicios de la cooperativa de taxis cotur del cantón Quevedo periodo 2013 - Quintana Zabala, Isabel Cristina (2015)
In this research project will make a special administrative management review, to publicize the shortcomings that are springing up both inside and outside the institution evaluating compliance with policies, goals and performance of the functions of administrative processes, will be assessed vehicle transport service taxi from the city of Quevedo, is a prime time to move to and from your home and other places requested by customers, need the objective is to conduct a special review of the administrative management and its impact on the quality of services of the taxi cooperative COTUR period 2013. Quevedo Canton have been implemented some methodologies for the investigative process, in this case the COSO I, which includes the risk Appraisal of the five components and achieve levels get applied trust and risk. With the analysis of administrative management and evaluation of the quality of services findings they were detected through surveys, interviews and direct observation of processes executed in the institution. In terms of the assessment of internal control resulted in a confidence level of 55.86% which means an average level and a level of risk that 44.14% is rated as Medium, when assessing the risk inherent led to 87.00% result is rated as high risk and detection of 5%. To assess these risks a risk review of 2.43% was obtained, this means that risk is under review. It is recommended that the risk assessment periodically and will be achieved detect weaknesses of the cooperative, you can minimize or reduce the weaknesses and to implement improvements to internal control.